Establishing the 99th percentile for high sensitivity cardiac troponin I in healthy blood donors from Southern Italy - Agnello, Luisa (Array, 2019)
Introduction: The knowledge of high sensitivity cardiac troponin I (hsTnI) distribution in a reference population is mandatory for its introduction in clinical practice. The aim of this study was to define the Upper Reference Limit (URL) of hsTnI measured by Single Molecule Counting technology (SMC) in an accurately selected reference population.Materials and methods: In the study 1140 blood donors were included and selected on the basis of medical history and biomarkers. High sensitivity cardiac troponin I was measured by SMC technology (Clarity, Singulex, Alamed, USA). The 99th percentile was calculated by the non-parametric method according to the Clinical and Laboratory Standard Institute - CLSI C28-A3.Results: The median age was 41 years (IQR: 28 - 50) and 69% were males. The overall 99th percentile was 5 ng/L (90% CI: 4.2 - 5.6). When considering sex-related differences, we found slight differences between the 99th percentile in males and females. Moreover, the 99th percentile trended with age, especially in females.Conclusions: We defined the 99th percentile of hs-cTnI measured by SMC technology in a highly selected healthy population, with only minor differences between males and females. Our findings provide the basic criteria for the reliable interpretation of hsTnI concentrations measured by the SMC technology in clinical settings.